Web-based smart career guide for EEE MSc Students - Tey, Kai Li (Nanyang Technological University, 2023)
Securing a desired career upon completing postgraduate study is of paramount importance and a goal to Electrical and Electronics Engineering (EEE) Master of Science (MSc) students. Most of MSc students are international students, as such, they are unfamiliar with the job application process in Singapore and the right application materials to prepare for it. Upon graduation, they are mostly unable to land their desired job in Singapore. This Final Year Project is focused on the design and development of a full-stack web application. The web application aims to provide a comprehensive platform that smartly guides international students in their career development from start to finish on their job application, which includes career searching, career preparation and career application. With exclusive job opportunities offered, to MSc students, MSc students can greatly increase their chances of securing their desired job. Additionally, they can leverage on the smart job searching platform to discover a career that align with their skillset.